Neoadjuvant camrelizumab plus chemotherapy for resectable, locally advanced esophageal squamous cell carcinoma (NIC‐ESCC2019): A multicenter, phase 2 study. Issue 1 (21st March 2022) - Liu, Jun; Li, Jingpei; Lin, Wanli; Shao, Di; Depypere, Lieven; Zhang, Zhifeng; Li, Zhuoyi; Cui, Fei; Du, Zesen; Zeng, Yuan; Jiang, Shunjun; He, Ping; et al.
Abstract: Optimal treatment for resectable esophageal squamous cell carcinoma (ESCC) is controversial, especially in the context of potential benefit of combining PD‐1 blockade with neoadjuvant therapy. This phase 2 study aimed to assess neoadjuvant camrelizumab plus chemotherapy in this population. Patients (clinical stage II‐IVA) received two cycles of neoadjuvant chemoimmunotherapy (NIC) with camrelizumab (200 mg on day 1) plus nab‐paclitaxel (260 mg/m 2 in total on day 1 and day 8) and cisplatin (75 mg/m 2 in total on days 1‐3) of each 21‐day cycle. Surgery was performed approximately 6 weeks after completion of NIC. Primary endpoint was complete pathologic response (CPR) rate in primary tumor. Secondary endpoints were objective response rate (ORR) per RECIST v1.1, 2‐year progression‐free survival (PFS) rate after surgery, PFS, overall survival (OS) and safety during NIC and perioperative period. Between 17 January 2020 and 8 December 2020, 56 patients were enrolled, and 51 received esophagectomy. Data cutoff date was 25 August 2021. The CPR rate was 35.3% (95% CI, 21.7%‐48.9%). NIC had an ORR of 66.7% (95% CI, 40.0%‐70.4%) and treatment‐related adverse events (TRAEs) of low severity (grade 1‐2, 75.0%; grade 3, 10.7%; grade 4‐5, no). No perioperative mortality occurred. Three (5.9%) patients had tumor recurrence and one (2.0%) patient died. The 2‐year PFS rate, median PFS and median OS had not been reached yet. Camrelizumab plus neoadjuvant chemotherapy in resectable ESCC demonstrates promising efficacy with acceptable toxicity, providing a feasible and effective option. Study is ongoing for long‐term survival analyses. Abstract : What's new? Adverse events linked to neoadjuvant chemoradiotherapy (CRT) for locally advanced, resectable esophageal squamous cell carcinoma (ESCC) significantly impact patient outcomes. Hence, there is critical need for radiation‐free therapies for ESCC. Here, the use of neoadjuvant chemoimmunotherapy (NIC) with camrelizumab plus chemotherapy was assessed in patients with resectable ESCC. Preoperative camrelizumab plus nab‐paclitaxel‐cisplatin resulted in complete pathologic response (CPR) in primary tumors and lymph nodes in more than 31% of patients—comparable to CPR rates for CRT. Adverse events with NIC, however, were less severe than CRT, warranting additional investigation of NIC with camrelizumab plus chemotherapy for resectable, locally advanced ESCC.